Genetic Epidemiology of Medication Safety and Efficacy Related Variants in the Central Han Chinese Population With Whole Genome Sequencing - Tian, Junbo; Zhang, Jing; Yang, Zengguang; Feng, Shuaisheng; Li, Shujuan; Ren, Shiqi; Shi, Jianxiang; Hou, Xinyue; Xue, Xia; Yang, Bei; Xu, Hongen; Guo, Jiancheng (Frontiers in Pharmacology, 2022)
Medication safety and efficacy-related pharmacogenomic research play a critical role in precision medicine. This study comprehensively analyzed the pharmacogenomic profiles of the central Han Chinese population in the context of medication safety and efficacy and compared them with other global populations. The ultimate goal is to improve medical treatment guidelines. We performed whole-genome sequencing in 487 Han Chinese individuals and investigated the allele frequencies of pharmacogenetic variants in 1,731 drug response-related genes. We identified 2,139 (81.18%) previously reported variants in our population with annotations in the PharmGKB database. The allele frequencies of these 2,139 clinical-related variants were similar to those in other East Asian populations but different from those in other global populations. We predicted the functional effects of nonsynonymous variants in the 1,731 pharmacogenes and identified 1,281 novel and 4,442 previously reported deleterious variants. Of the 1,281 novel deleterious variants, five are common variants with an allele frequency >5%, and the rest are rare variants with an allele frequency <5%. Of the 4,442 known deleterious variants, the allele frequencies were found to differ from those in other populations, of which 146 are common variants. In addition, we found many variants in non-coding regions, the functions of which require further investigation. This study compiled a large amount of data on pharmacogenomic variants in the central Han Chinese population. At the same time, it provides insight into the role of pharmacogenomic variants in clinical medication safety and efficacy.